Ius Constituendum Regulates the Cadre-Based Recruitment of Candidates for Members of the House of Representatives Through Political Parties - Mukhlis, Muhammad Mutawalli; Ruslan, Achmad; Wahid, A.M. Yunus; Ilyas, Anshori; Wahab, Harlida Abdul (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2024)
This study seeks to examine the challenges associated with cadre-based recruitment of the House of Representative candidates by political parties and to propose ideal frameworks for such recruitment. The current processes of political party recruitment are not comprehensive and encounter philosophical, sociological, and juridical issues. Philosophically, recruitment practices and orientations differ widely among parties, with some adopting populist methods and others being controlled by party elites. Sociologically, a feudalistic political culture ties parties to certain figures, promoting a pragmatic approach aimed at winning elections rather than ensuring candidate quality. Juridically, while Law Number 2 of 2011 mandates democratic cadre recruitment, Law Number 7 of 2017 on General Elections lacks clear requirements for nominating cadres, resulting in inconsistencies between the laws. This research employs a normative legal methodology, incorporating conceptual, statutory, and comparative approaches. The study involves analyzing regulatory documents, books, journals, and other relevant scholarly works to explore how legal provisions are implemented in society. The findings indicate that problems in cadre-based recruitment arise from ambiguous principles and orientations in regulations. Future arrangements should prioritize party ideology and orientation, drawing on practices from Malaysia and the United States. It is crucial to establish statutory principles for political party cadre and recruitment, focusing on character, utility, ideology, vote balance, democracy, transparency, justice, and equality.